Pendampingan Rencana Pembangunan dan Perencanaan Permukiman Kumuh di Kabupaten Sarmi - Sudiro Sudiro; Tommi Tommi; Marshal A Lamba; Lazarus Ramandei; Julian Wairata (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
The fulfillment of basic human needs for clothing, food and shelter is an important factor in community welfare. However, the problems faced in Sarmi Regency show that supporting documents regarding housing and settlement conditions in the administrative area are not yet available. This community service activity pays attention to the potential and challenges faced by Sarmi Regency, including the need for decent housing, sustainable residential area development, and the need to improve adequate basic infrastructure and public facilities. This activity uses collaborative planning methods divided into 3 stages: preparation, implementation, and evaluation stages. Community service activities were carried out during November-December 2024. The results of this activity were fact reports and analysis of housing and settlement status in Sarmi Regency.